Effect of force symmetry on coordination in crawl - Tourny-Chollet, C.; Seifert, L.; Chollet, D. (International Journal of Sports Medicine, 2009)
The relationship between breathing laterality and motor coordination symmetry as a function of the symmetry of medial rotator muscle force in the shoulders was investigated. The principal objective was to distinguish swimmer profiles. Thirteen expert male swimmers performed the front crawl and were assessed for: (i) inter-arm coordination with the IdC and arm coordination symmetry with the Symmetry Index, (ii) breathing laterality, and (iii) the symmetry of the isokinetic force in the shoulder medial rotators. The results indicated that the relative duration of catch+pull was greater for the dominant arm (51.7%) than for the non-dominant arm (48.4%) for the swimmers with force asymmetry (p<0.05) and occurred on the side with the higher force (dominant arm). Two profiles were revealed: (i) swimmers for whom breathing laterality was related to force symmetry and stroke phase duration and (ii) swimmers for whom the impact of breathing laterality on force symmetry and stroke duration was low. The first profile corresponded to sprint specialists and the second profile corresponded more to middle-distance specialists.